UPAYA PENINGKATAN KESELAMATAN LALU LINTAS PADA PERSIMPANGAN TAK BESINYAL RAWAN KECELAKAAN DI JALAN NASIONAL KABUPATEN KAMPAR - Benny Hamdi Rhoma Putra; Elianora Elianora; Sri Djuniati; Rizqy Ridho Prakasa; Novreta Ersy Darfia (Racic : Rab Construction Research, 2025)
The high rate of accidents at unsignalized intersections in Kampar Regency is one of the reasons for conducting this research. Data from the State Police of the Republic of Indonesia in the Kampar Sector recorded 1,013 accident cases between 2017 and 2020. The purpose of this study was to select accident-prone locations based on the results of ranking the highest accident rates, analyze safety issues, and provide recommendations for handling these locations. The ranking analysis was carried out using accident data for 4 years using the ACF and EPDO methods. Based on the ranking results, two locations are accident-prone areas, namely Jl Pekanbaru-Bangkinang KM 40 and Jl Pasir Putih KM 07. The problem of traffic safety on the Pekanbaru-Bangkinang KM 40 road is the time of accidents that occur during the day and night with the type of rear accident. end, single, head on. Traffic conflicts that occur are slowing down in the same direction, changing lanes, turning right in the same direction and turning left in the same direction. Some of the obstacles that occur include, there are no warning signs, road markings are unclear, visibility is disturbed by bushes, no PJU, roads that have not been paved, no road nails, and damaged pavement. Recommendations that can be suggested include repairing road pavements, clearing bushes at intersections, making PJUs, warning signs for accident-prone areas, caution signs, making road spikes. At the location of Jalan Pasir Putih KM 07 the problem of traffic safety is when the accident occurred during the day, with the type of head on accident. Traffic conflicts slow down in one direction, change lanes, turn right in the same direction and turn left in the same direction. Traffic management has no warning signs, plants that interfere with the driver's line of sight, vehicles parked haphazardly, unclear road markings, no road spikes, no PJU, damage to road pavement. The recommendations for handling are repairing road damage, repairing road markings, clearing land from plants that interfere with driver's visibility, signs prohibiting parking, making road spikes, warning signs for accident-prone areas, caution signs.